Understanding of Breast Cancer and SADARI Through Audio-Visual Health Education for Adolescents at Mutiara 2 High School Bandung - Oryza Tri Novita Oryza (Journal of Health Community Service, 2022)
Lack of knowledge about breast cancer and never having a breast examination are factors that cause delays in breast cancer diagnosis. Proper education in health education is one of the primary keys to influencing knowledge. The implementation of this service activity aims to provide health education with audio-visual so that the insight and knowledge of adolescents will be better. Health education is carried out through WhatsApp group media which contains information about breast cancer and SADARI examination with the stages of making leaflets about breast cancer and SADARI, making videos about SADARI steps, measuring adolescent student knowledge by giving several questions in the form of a questionnaire about breast cancer and SADARI, evaluates health education for adolescent students by discussing and assessing the answers to the questionnaires that have been filled out by students. This service activity show an increase in the knowledge of young women before and after being given health education. The school can consider this activity to provide information support and motivation with various learning methods so that young women continuously get updated information in education and health knowledge. There is an increase in respondents’ knowledge after being given health education using audiovisual (60.0%) in the good category, which was previously only (13.3%) and the sufficient category (40.0%) and no less category.